NALCO Guide to Cooling Water System Failure Analysis - Herro, H.M. (McGraw-Hill Companies, 2011)
This handbook covers a wide variety of environments and equipment, including open and closed systems, recirculating and once-through arrangements, conventional shell-and-tube exchangers and plate heat exchangers, special purpose cooling arrangements, and service water systems.